Coordinated and Multiple Views in Exploratory Visualization (CMV'05)
DOI: 10.1109/cmv.2005.1
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Multi-View Virtual Environment for Molecular Visualization and Modeling

Abstract: Molecular modeling has been a long-standing research area for biologists. However, the existing molecular modeling software lacks strong support for collaborative research. In this paper we describe our effort to develop a collaborative multi-view virtual environment for molecular visualization and modeling. In our virtual environment, the users are able to visualize large molecular structures in real-time, create their own view, or share their view with others in the system. The system allows for individual o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…240 Different studies demonstrated the possible benefits of immersive and interactive approaches in education, [241][242][243][244] and multiple virtual reality frameworks were designed for simultaneous immersion of multiple persons, allowing for collaborative environments. 192,[245][246][247][248][249]…”
Section: Interactive Approaches In Classical Simulationsmentioning
confidence: 99%
“…240 Different studies demonstrated the possible benefits of immersive and interactive approaches in education, [241][242][243][244] and multiple virtual reality frameworks were designed for simultaneous immersion of multiple persons, allowing for collaborative environments. 192,[245][246][247][248][249]…”
Section: Interactive Approaches In Classical Simulationsmentioning
confidence: 99%
“…Some theme-related works are: VRDD [2], Distributed PaulingWorld [3] [4], Jmol adapted for collaborative use [5], Interactive Molecular Visualization System [6], AMMP-Vis [7] [8] KinImmerse.…”
Section: Introductionmentioning
confidence: 99%
“…For making the interaction more efficient with such huge spaces of data, few existing interactive systems in bioinformatics are based on post-WIMP [12] interfaces [1,13,10,31,30,27]: they are mainly based on the immersion of the user within the 3D structure. For example in [1,13,10], the visualization techniques are implemented in CAVEs (automated virtual environment) to dynamically simulate the physical and chemical properties of the molecular system. As opposed to these systems based on an immersive environment, interaction with NAVRNA is based on an augmented collaborative environment made of interactive surfaces (a table and a whiteboard).…”
Section: Algorithmmentioning
confidence: 99%